In situ control of radial vortex polarity at room temperature utilizing perpendicular magnetic field pulse. (16th October 2019) - Li, Cheng; Fang, Liang; Yang, Xiaokuo; Xu, Nuo; Liu, Baojun; Wei, Bo; Zhou, Errui; Yang, Binbin
Abstract: In this paper, the in situ control of radial vortex polarity and chirality at room temperature mediated by perpendicular magnetic field pulse has been reported via micromagnetic simulations. The correlative results show that the polarity and chirality are switched simultaneously without resulting in a large core movement, the simulation built-in magnetic force microscopy provides a deeply insight into the evolution of magnetic configuration during the reversal process. The reversal mechanism reported in this work differs from the reported vortex-antivortex pair creation and annihilation mechanisms, which is useful for bit reading and probing in magnetic data storage devices. Meanwhile, the thermal perturbations at nonzero temperatures will weaken the effect of magnetic field, so the threshold field strength need increase with the elevated temperature to guarantee chirality and polarity reversed completely. This approach presents an alternative efficient means to achieve an ultrafast radial vortex chirality and polarity switching, which paves the way for the practical application of magnetoresistive memory based on radial vortex.